Measuring professionals’ perceptions about collaborative consultation in early childhood intervention - Boavida, T.; Silva, C. S.; Aguiar, C.; McWilliam, R. A. (International Journal of Inclusive Education, 2022)
We investigated the reliability and construct validity of the Professionals’ Perceptions about Collaborative Consultation in Early Childhood Intervention Scale (ProPerCECIS), a rating scale developed to measure collaborative consultation in early childhood intervention (ECI). ProPerCECIS was completed by 427 professionals from 78 ECI teams. The full sample was randomised into sample A, 170 participants, for conducting an exploratory factor analysis (EFA) – and sample B, 257 participants, for performing confirmatory factor analysis (CFA). Multiple-group analysis, with the overall sample, was conducted. The EFA final solution comprised three correlated factors, with acceptable to very good internal consistency: Intervention, Context, and Planning. The CFA supported the three-factor structure. Results supported configural invariance and partial metric invariance, but partial scalar invariance did not hold. Results supported the conceptual framework of collaborative consultation in ECI and suggest that ProPerCECIS can be a useful measure of professionals’ perceptions about collaborative consultation practices in ECI. ProPerCECIS seems to be particularly suited to assess collaborative practices within services providing routines-based family-centred interventions. Importantly, because the factor structure for ProPerCECIS holds up for different professional groups, it might be used by transdisciplinary ECI teams.